2007
DOI: 10.1161/01.res.0000255031.15793.86
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Role of Tumor Necrosis Factor-α in Coronary Microembolization

Abstract: Abstract-In patients with unstable angina, plaque rupture and coronary microembolization (ME) can precede complete coronary artery occlusion and impending infarction. ME-induced microinfarcts initiate an inflammatory reaction with increased tumor necrosis factor-␣ (TNF-␣) expression, resulting in progressive contractile dysfunction. However, TNF-␣ is not only a negative inotrope but can also protect the myocardium against infarction. In anesthetized pigs, we studied whether ME protects against infarction when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…The combination of inflammatory cells and thrombi inside the blood vessels in subacute microinfarction may contribute to LV dysfunction (9,10,(48)(49)(50). The pattern of microinfarction crossing the LV wall was similar to that observed at autopsy in patients with coronary microembolization (43,51).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The combination of inflammatory cells and thrombi inside the blood vessels in subacute microinfarction may contribute to LV dysfunction (9,10,(48)(49)(50). The pattern of microinfarction crossing the LV wall was similar to that observed at autopsy in patients with coronary microembolization (43,51).…”
mentioning
confidence: 68%
“…Other investigators (47) also found a lack of correlation between regional function, by using electron-beam CT in beating hearts, and microinfarction volume, by using micro-CT in the excised hearts. This mismatch was attributed to the presence of inflammation, mediated by tumor necrosis factor-␣ around the microinfarcted region (periinfarction zone) (9,10,(48)(49)(50).…”
Section: Experimental Studies: Microinfarction After Coronary Microemmentioning
confidence: 99%
“…24 Whereas the present study revealed major differences in signal transduction by RISK between rodents and pigs, both sphingosine 25 and STAT3 26 are parts of the signal transduction of tumor necrosis factor (TNF)␣-induced cardioprotection, TNF␣-induced cardioprotection does not rely on AKT and ERK1/2, 26 and TNF␣ is also cardioprotective in pigs. 27 Thus, the role of STAT3 and sphingosine kinase in ischemic postconditioning in pigs or other large mammals should be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition, accumulation of endogenous TNF-␣ after coronary microembolization reduces infarct size. 9 Finally, the protection of delayed ischemic preconditioning is absent after pretreatment with TNF-␣ antibodies and in TNF-␣-, TNFR1-, and TNFR2-knockout mice 13 ; the latter result reflects the involvement of both TNFRs in cardioprotection. 13,14 …”
Section: Tnf-␣ and Cardioprotectionmentioning
confidence: 98%
“…TNF-␣ contributes to both reversible (contractile dysfunction 4,9 ) and irreversible (MI) injury. 1 Preischemic treatment with TNF-␣ antibodies 10 or soluble TNFR1, 11 permanent TNF-␣ knockout, 12 or knockout of TNFR1 but not TNFR2 13 all reduce infarct size.…”
Section: Tnf-␣ and Myocardial Ischemia/ Reperfusion Injurymentioning
confidence: 99%